The Tracefile Testbed: a community repository for identifying and retrieving HPC performance data. (11th November 2005) - Ferschweiler, Ken; Harrah, Scott; Keon, Dylan; Calzarossa, Mariacarla; Tessera, Daniele; Pancake, Cherri
HPC programmers utilise tracefiles, which record program behaviour in great detail, as the basis for many performance analysis activities. The lack of generally accessible tracefiles has forced programmers to develop their own testbeds in order to study the basic performance characteristics of the platforms they use. Because tracefiles serve as input to performance analysis and performance prediction tools, tool developers have also been hindered by the lack of a testbed for verifying and fine-tuning tool functionality. A community repository that meets the needs of both application and tool developers has been created in this study. In this paper, we describe how the Tracefile Testbed was designed to facilitate flexible searching and retrieval of tracefiles based on a variety of characteristics has been described. Its web-based interface provides a convenient mechanism for browsing, downloading, and uploading collections of tracefiles and tracefile segments, as well as viewing statistical summaries of performance characteristics.